The Impact of Global Financial Crisis and the Performance of Malaysian SMEs - Wong, Shuh Yin (2010)
This research paper served the purpose of examining the impact of global financial crisis (GFC) on the Malaysian small and medium-sized enterprises (SMEs), with focus mainly on the manufacturing and services sectors. The small and medium enterprises (SMEs) significantly influence the economic growth of both developed and developing countries (Hashim, 1999 & 2000). SMEs in Malaysia play an important role in the country‟s economic development. According to SME Annual Report 2008, SMEs represent majority of the businesses in Malaysia, constituting 99.2% of total establishments in the three main economic sectors of manufacturing, services and agriculture. The overall purpose of this paper is to gain insights into the dimensions of manufacturing and services sectors in Malaysian SMEs being impacted by GFC; and to arrive at a better understanding on what had affected the differences in intensity of impact among them, hence the possibility of creating a mutual learning opportunity among the Malaysian SMEs especially among the same sector. By studying the dimensions of manufacturing and services sectors in Malaysian SMEs being impacted by GFC, thereby identifying and analysing the factors that affecting their performance during GFC, which have not been appreciated, recognised or factored into the management of the SME. The attempt of this study will contribute to knowledge and experience sharing and enhance practices in the management of SMEs in Malaysia. Furthermore, this will enable the government and related bodies to gain insights of SMEs and combine the adoptable management practices with appropriate mix of policies and support schemes to achieve the target set, which is to increase the contribution of SMEs to Gross Domestic Product (GDP). Nonetheless, this study will also contribute to the future relevant research.